Constraining type Ia supernovae progenitors from three years of supernova legacy survey data - Bianco, F; Howell, D; Sullivan, M; Conley, A; Kasen, D; Gonzlez-Gaitn, S; Guy, J; Astier, P; Balland, C; Carlberg, R; Fouchez, D; Fourmanoit, N; et al. (2011)
While it is generally accepted that Type Ia supernovae are the result of the explosion of a carbon-oxygen white dwarf accreting mass in a binary system, the details of their genesis still elude us, and the nature of the binary companion is uncertain. Kasen points out that the presence of a non-degenerate companion in the progenitor system could leave an observable trace: a flux excess in the early rise portion of the light curve caused by the ejecta impact with the companion itself. This excess would be observable only under favorable viewing angles, and its intensity depends on the nature of the companion. We searched for the signature of a non-degenerate companion in three years of Supernova Legacy Survey data by generating synthetic light curves accounting for the effects of shocking and comparing true and synthetic time series with Kolmogorov-Smirnov tests. Our most constraining result comes from noting that the shocking effect is more prominent in the rest-frame B than V band: we rule out a contribution from white dwarf-red giant binary systems to Type Ia supernova explosions greater than 10% at the 2σ, and greater than 20% at the 3σ level. © 2011 The American Astronomical Society. All rights reserved.